Professors' didactic performance and students' didactic performance in psychology classes at a Peruvian university - Bazán-Ramírez, Aldo; Henostroza-Mota, Carmela Reynalda; Peña-Correa, Giovanna Britt; Capa-Luque, Walter; Mayorga-Falcón, Luz Elizabeth; Begazo-Jaramillo, Adrián Ernesto; Quicaña-Amau, Fernando Paolo (Frontiers in Education, 2025)
The teaching-learning of the psychological discipline involves teacher-student interactions, which are structured under different criteria of didactic performance in the various practices of psychological teaching. The present research was conducted under the interbehavioral model of didactic performance that includes seven didactic criteria of teacher performance and six criteria of student didactic performance. Forty-nine regular teachers and 541 students from the Faculty of Psychology of a public university in Lima participated. The teachers answered an online self-assessment questionnaire about their performance on seven didactic criteria, and the students also answered an online self-assessment questionnaire about their performance on six didactic criteria. The results showed significant but negative correlations between the teacher's didactic performance in Illustration and Evaluation with all the students' didactic performances, and a significant and positive relationship of the teacher's didactic performance in Didactic Planning with all the students' didactic performances. Likewise, it was found that the didactic performance of the self-assessed students was significantly predicted by the level of studies in which the subject is taught (basic or initial, intermediate or advanced), by the teacher's performance in Didactic Planning, Competence Exploration, Evaluation, and by the teacher's experience in teaching psychology.